2000
DOI: 10.1115/1.1336798
|View full text |Cite
|
Sign up to set email alerts
|

Local Dynamic Stability Versus Kinematic Variability of Continuous Overground and Treadmill Walking

Abstract: This study quantified the relationships between local dynamic stabiliht and variabilitr during continuous overground and treadmill walking. Stride-to-stride standard deviations were computed from temporal and kinematic data. Marimum finite-time Lyapunov exponents were estimated to quantify local dynamic stability. Local stability of gait kinematics was shown to be achieved over multiple consecutive strides. Traditional measures of variability poorly predicted local stability. Treadmill walking was associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

36
430
4
5

Year Published

2002
2002
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 573 publications
(475 citation statements)
references
References 28 publications
36
430
4
5
Order By: Relevance
“…Furthermore, we used treadmill walking instead of overground walking to produce robust estimates of step variability. The corollary is that treadmill walking has been found to be associated with a reduction of variability (Dingwell et al 2001), which may have masked some dual-task related gait changes as previously mentioned.…”
Section: Discussionmentioning
confidence: 87%
“…Furthermore, we used treadmill walking instead of overground walking to produce robust estimates of step variability. The corollary is that treadmill walking has been found to be associated with a reduction of variability (Dingwell et al 2001), which may have masked some dual-task related gait changes as previously mentioned.…”
Section: Discussionmentioning
confidence: 87%
“…Due to the spatial constraints of the video motion capture system; a treadmill was necessary to enable collection of kinematic data across many sequential strides. Studies have shown that a treadmill may reduce kinematic variability and increase dynamic stability of gait measures [7]. Finally, our results were limited to healthy adults.…”
Section: Discussionmentioning
confidence: 89%
“…Still, in young as well as in older subjects, around mid-swing either of these strategies could be elicited. After tripping on a treadmill the transition between strategies was more distinct (Schillings et al 2000), which might be explained by lower variation of stride length and duration in treadmill walking (Dingwell et al 2001). However, the occurrence of both strategies in the same part of the gait cycle overground suggests that strategy selection is not heavily constrained, i.e., either one could be adequate.…”
Section: Timing and Sequencing Of Muscle Activationmentioning
confidence: 98%